Implementation of Total Physical Response (TPR) Method in Teaching Arabic Vocabulary: A Study in Junior High Schools Al-Muttaqin Besitang - Amalia, Ariza; Rahmaini, Rahmaini (Universitas Yudharta Pasuruan, 2025)
This study is motivated by the problem of students’ low mastery of mufrodat (vocabulary) and their learning motivation in Arabic language subjects, which are often perceived as boring. The study aims to describe the implementation of the Total Physical Response (TPR) method, its effectiveness in improving vocabulary mastery, and to identify inhibiting factors in its application among eighth-grade students at MTs Al-Muttaqin Besitang. The study employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results show that the implementation of TPR through the stages of introduction, demonstration, and random commands successfully created a dynamic and enjoyable learning atmosphere. This method proved effective in enhancing students’ memory retention and comprehension of vocabulary meanings through physical movement associations, as well as increasing students’ enthusiasm and active participation in class. However, there were several inhibiting factors, primarily micro-instructional issues such as the teacher’s fast speech tempo and unclear movement modeling, along with environmental constraints such as limited classroom space. The study concludes that the TPR method is highly relevant for the characteristics of active madrasah students, but improvements are needed in the aspects of instructional delivery and classroom management to achieve more optimal learning outcomes.